Amanat Undang-Undang Partai Politik terhadap Partisipasi Kader Perempuan Dalam Pemilihan Umum - Primayanti, Andi Dewi; Bruaharja, Isman (Amsir Law Journal, 2023)
The general election in 2009 is one that is highlighted in this article regarding the role of women in political contestation. Positive policy with a quota of 30 percent for women in the establishment and formation of political parties and political party leadership based on several articles in Law Number 2 of 2008 concerning Political Parties. The representation of women is a hope in changing the political scene in this country. This law opens many opportunities for women to fight in politics. The approach method used in this research is the juridical-normative method. This method is carried out through literature studies on various literature related to legal theories and principles. The answers came from women in participating in the political space. Starting from those who work as vegetable sellers to housewives who are not affiliated with any organization. Law Number 2 of 2008 concerning Political Parties regulates women’s representation of 30 percent in establishing political parties and leading political parties. ___ Referensi Buku dengan penulis: Anugrah, Astrid. (2009). Keterwakilan Perempuan Dalam Politik. Jakarta: Pancuran Alam. Asshiddiqie, Jimly. (2014). Menegakkan Etika Penyelenggara Pemilu. Jakarta: PT Radja Grafindo Persada. Bressler, Charles E. (1999). Literary Criticism: An Introduction to Theory and Practice. Upper Saddle River, N.J.: Prentice Hall. Hadiz, Liza (ed.). (2004). Perempuan Dalam Wacana Politik Orde Baru: Pilihan Artikel Prisma. Jakarta: LP3ES. Mahfud MD., Moh. (2006). Membangun Potik Hukum Menegakkan Konstitusi. Jakarta: LP3ES. Soekanto, Soerjono., dan Mamudji, Sri. (2001). Penelitian Hukum Normatif: Suatu Tinjauan Singkat. Jakarta: PT Radja Grafindo Persada. Yuhana, Abdi. (2001). Sistem Ketatanegaraan Indonesia Pasca Perubahan UUD 1945. Bandung: Fokusmedia. Artikel jurnal: Artina, D. (2016). Keterwakilan Politik Perempuan dalam Pemilu Legislatif Provinsi Riau Periode 2014-2019. Jurnal Hukum Ius Quia Iustum, 23(1), 123-141. Kiranantika, A. (2022). Memahami Interseksionalitas Dalam Keberagaman Indonesia: Tinjauan dalam Sosiologi Gender. Indonesian Journal of Sociology, Education, and Development, 4(1), 48-55. Listyani, R. H. (2016). Perempuan Dalam Politik Maskulin. Al’Adalah, 17(2), 307-322. Manurung, R. T. (2009). Ketidakberpihakan Jargon Politik terhadap Perempuan di Indonesia. Jurnal Sosioteknologi, 16(8), 552-558. Nimrah, S., & Sakaria, S. (2015). Perempuan dan Budaya Patriarki Dalam Politik: Studi Kasus Kegagalan Caleg Perempuan Dalam Pemilu Legislatif 2014. The Politics: Jurnal Magister Ilmu Politik Universitas Hasanuddin, 1(2), 173-181. Parwati, T., dan Istiningdiah, K. (2020). Partisipasi dan Komunikasi Politik Perempuan di Legislatif menurut Kacamata Politisi Perempuan di Indonesia. Interaksi: Jurnal Ilmu Komunikasi, 9(2), 119-29. Squires, Judith. (2007). State Feminism and Political Representation, Parliamentary Affairs, 60(1), 170-179. Thalib, N. A. (2014). Hak Politik Perempuan Pasca Putusan Mahkamah Konstitusi (Uji Materiil Pasal 214 Undang-Undang Nomor 10 Tahun 2008). Jurnal Cita Hukum, 2(2), 233-248. World Wide Web: Mazrieva, Eva. (2022). Mengapa Perempuan Tak Kunjung Capai Kuota 30% di DPR?, https://www.voaindonesia.com/a/mengapa-perempuan-tak-kunjung-capai-kuota-30-di-dpr-/6452476.html Diakses pada tanggal 20 Oktober 2022.